Contribuição das universidades para a Agenda 2030: um enfoque a partir das atividades extensionistas da UFG - Junqueira, Maíra Cinquini (2025)
The overall objective of this study is to map the SDGs present in the extension activities of the Federal University of Goiás. To achieve this, an exploratory and quantitative research approach was adopted, using keyword search as the mapping strategy. For its implementation, it was necessary to develop a classification algorithm and compile a list of keywords. The data obtained from the mapping were analyzed using descriptive statistical techniques and presented in the form of graphs and tables. It was found that out of a total of 10,980 extension actions analyzed, 8,179 were linked to at least one of the SDGs. This number represents 74% of the total evaluated actions, highlighting a significant connection between the university's extension initiatives and the goals proposed by the 2030 Agenda. SDG 4 (Quality Education) led the ranking, being associated with 6,297 initiatives, followed by SDG 3 (Good Health and WellBeing), linked to 2,447 actions. Together, these two accounted for approximately 72% of the total frequency of extension actions. We conclude that the obtained results demonstrate the university's potential contribution to advancing the 2030 Agenda, particularly through its extension activities. As a technical contribution, the development of an automated mapping tool stands out. The presence of all SDGs in UFG's extension activities also highlights the institution's social impact. Finally, as a theoretical contribution, we emphasize that the results can serve as a basis for further research and academic work, helping to expand discussions on the topic. Additionally, these contributions strengthen the institution's image by associating it with the 2030 Agenda, enhancing its positioning in university rankings and opening pathways for partnerships with organizations aligned with sustainable development. As the Technological Technical Product of this dissertation, a tutorial on the mapping process is presented, enabling its replication by UFG or other educational institutions